Uso de substratos no cultivo do camarão branco (Litopenaeus vannamei) em sistema superintensivo - Souza Filho, Wilson Justiniano de (Universidade Federal Rural do Semi-Árido, 2019)
Aquaculture is the activity that cultivates aquatic organisms, at any stage of their development, in confined and controlled environments. The present work consists of evaluating the zootechnical development of the white shrimp Litopenaeus vannamei, grown in high stocking densities, using vertical and horizontal substrates. Individual weight gain, final biomass, apparent feed conversion factor (FCAA) and survival were analyzed. The experiment had 3 treatments: control (C), vertical substrate (V) and horizontal substrate (H), using 20% of the tank area in the latter two. Each tank had 2400 prawns with a density of 160 prawns/m². The water analysis was done twice a week, and the following parameters were verified: temperature, dissolved oxygen in the water, transparency, salinity and pH, being compliant for the cultivation of white shrimp. Statistical analysis was not significant for treatments.
Monografia
Keywords: Altas desidades; Camarão branco; Substrato; High disturbances; White shrimp; Substrate; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA